2019
DOI: 10.1101/590158
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Macro-to-nano scale investigation of wall-plate joints in the acorn barnacle Semibalanus balanoides: correlative imaging, biological form and function, and bioinspiration

Abstract: 1.AbstractCorrelative imaging combines information from multiple modalities (physical-chemical-mechanical properties) at various length-scales (cm to nm) to understand complex biological materials across dimensions (2D-3D). Here, we have used numerous coupled systems: X-ray microscopy (XRM), scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), optical light microscopy (LM), and focused-ion beam (FIB-SEM) microscopy to ascertain the microstructural and crystallographic properties of the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…In their EBSD study on the alae of Semibalanus balanoides, Mitchell et al [10] revealed areas of even orientations, which, in the absence of an SEM study, they interpreted as individual grains. Given their sizes, they are rather CCRs of the type recognized here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their EBSD study on the alae of Semibalanus balanoides, Mitchell et al [10] revealed areas of even orientations, which, in the absence of an SEM study, they interpreted as individual grains. Given their sizes, they are rather CCRs of the type recognized here.…”
Section: Discussionmentioning
confidence: 99%
“…At the base plate, the calcite crystals' c-axes are perpendicular to the base plate close to the substrate and later change to become parallel to the attachment surface towards the middle of the base plate. EBSD maps obtained on the margins of the alae in the horizontal section revealed crystalline domains with complex boundaries, which elongated perpendicular to the growth margin, thus having a radial arrangement [10]. The c-axes of these domains display a similar distribution.…”
Section: Introductionmentioning
confidence: 91%
“…Additional files supporting this article have been uploaded as part of the electronic supplementary material, S1–S4. XRM scans (tiff stacks) of whole barnacles mounted in resin and individual plates are available from the Dryad Digital Repository at: [74].…”
Section: Data Accessibilitymentioning
confidence: 99%
“…However, little is understood about how macro-micro-nanoscale structures, particularly in the shell, are linked. Correlative imaging provides an opportunity to discover the multiscale interactions and mechanisms involved in the structure of complex systems at varying length scales [26][27][28][29] and, specifically for barnacles, provides an opportunity to correlate optical, analytical, structural and mechanical information [30] for the first time. Here, we have coupled numerous systems at various length scales: X-ray microscopy (XRM), scanning electron microscopy (SEM), light microscopy (LM) and focussed ion beam microscopy (FIB-SEM) to ascertain the macro-to-nanoscale structure, crystallographic orientation and mechanical properties of wall-plate joints in the parietal exoskeleton of the barnacle Semibalanus balanoides.…”
mentioning
confidence: 99%